2002
DOI: 10.1034/j.1399-6576.2002.460415.x
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of a video program for presentation prior to elective cardiac surgery

Abstract: : We conclude from our results that (i); cardiac surgical patients prefer preoperatively an adjunct surgery-related video preparation to a non-specific video presentation, and that (ii); preoperative preparation with realistic information about the upcoming medical procedure in patients undergoing cardiac surgery does not lead to an increase in endocrine stress hormone levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…There was no statistically significant difference found between pre-operative and post-operative state-trait anxiety scores (p < 0.05). In the study of Roth-Isıgkeit and his friends, named Development and evaluation of a video program for presentation prior to elective cardiac surgery, it is concluded that The findings obtained in this study are consistent with the results of the studies indicating that training with visual tools is more effective than with other types of material [37]. Doering S. Behensky and his friends stated that "Preoperative presentation of videotapes is used as an adjunct method for the preparation of patients prior to surgery" in their study named.…”
Section: Discussionsupporting
confidence: 82%
“…There was no statistically significant difference found between pre-operative and post-operative state-trait anxiety scores (p < 0.05). In the study of Roth-Isıgkeit and his friends, named Development and evaluation of a video program for presentation prior to elective cardiac surgery, it is concluded that The findings obtained in this study are consistent with the results of the studies indicating that training with visual tools is more effective than with other types of material [37]. Doering S. Behensky and his friends stated that "Preoperative presentation of videotapes is used as an adjunct method for the preparation of patients prior to surgery" in their study named.…”
Section: Discussionsupporting
confidence: 82%
“…Black, overall total stress score; vertical lines, cognitive-emotional stress total subscore; gray, physiological stress total subscore; horizontal lines, overall mean anxiety score; checkerboard, separation anxiety mean subscore; white, panic disorder anxiety mean subscore; dashed lines, generalized anxiety mean subscore. surgery (Roth-Isigkeit et al, 2002). In children, outcomes of sensory-perceptual preprocedural education are less well known.…”
Section: Discussionmentioning
confidence: 98%
“…A significant rise of postoperative serum cortisol in cardiac surgery patients has been described in several studies over the last decades [30-34]. The rise of endocrine stress markers seems not to depend on the individual, anticipatory stress of the patient awaiting surgery, the type of postoperative respiratory weaning, perioperative beta blockade or sufentanil or fentanyl doses [35-39]. …”
Section: Discussionmentioning
confidence: 99%